2017
DOI: 10.1186/s12978-016-0272-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fertility desire among married or cohabiting individuals in Rakai, Uganda: a cross-sectional study

Abstract: BackgroundRecent trends in fertility rates indicate declines in total fertility rate (TFR) in some sub-Saharan African countries. However, countries such as Uganda continue to have a persistently high TFR partly attributed to strong preferences for large family sizes. We explored the factors that influence fertility desire among married or cohabiting individuals in Rakai, a rural district in southwestern Uganda.MethodsThis cross-sectional study of fertility desire (desire to have another child) was nested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
71
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 24 publications
25
71
6
1
Order By: Relevance
“…This is similar to another study which observed higher fertility desires among men (70%) compared to women (57%) in a similar setting [18]. When discordance in fertility desire was observed, more men compared to women had a desire for a (another) child.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to another study which observed higher fertility desires among men (70%) compared to women (57%) in a similar setting [18]. When discordance in fertility desire was observed, more men compared to women had a desire for a (another) child.…”
Section: Discussionsupporting
confidence: 90%
“…They establish homes when they move from one shing community to another in search for sh. Also culturally, African men tend to desire to have many children as has been observed in our study and in other studies on FP [1] because many children are associated with prestige, masculinity and respect in society [4]. All these make them prone to engaging in sexual relations which sometimes result into unwanted pregnancies.…”
Section: Discussionsupporting
confidence: 75%
“…Contraception helps families achieve their desired number of children and is instrumental in child spacing [1]. However, the number of children a couple may have and their child spacing interval tend to be in uenced by their knowledge and eventual use of contraception [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This poses challenges for safe motherhood and child survival as well as other development programmes aimed at improving the quality of life of the population at large. Family planning use is one of the public health interventions that needs to be promoted in Uganda because it helps families to achieve a desired number of children and is instrumental in child spacing [6]. By preventing pregnancy, family planning reduces pregnancy-related health risks in women [7], infant mortality and prevents teenage pregnancies [8].…”
Section: Introductionmentioning
confidence: 99%